Automated quantitative tumour response assessment of MRI in neuro-oncology with artificial neural networks: a multicentre, retrospective study - Vollmuth, Philipp; Pflüger, Irada; Petersen, Jens; Neuberger, Ulf; Brugnara, Gianluca; Schell, Marianne; Keßler, Tobias; Foltyn-Dumitru, Martha; Harting, Inga; Sahm, Felix; Prager, Marcel; Nowosielski, Martha; et al. (The lancet. Oncology, 2019)
We aimed to develop a framework relying on artificial neural networks (ANNs) for fully automated quantitative analysis of MRI in neuro-oncology to overcome the inherent limitations of manual assessment of tumour burden.